SOSIALISASI KEGIATAN PRAJA BHAKTI SEBAGAI PENGUATAN INTEGRASI BANGSA DI DESA MANGLI KECAMATAN KALIANGKRIK KABUPATEN MAGELANG - Endang Sri Kurniatun (JURNAL NAGARA BHAKTI, 2022)
In line with the increasingly complex challenges and problems faced by our Nation, the role of the Military Academy will be increasingly important in the context of supporting National integration. The initiative to initiate, discuss, and design programs that are commensurate and in line with these expectations, the Military Academy implements the Praja Bhakti program in Mangli, Kaliangkrik District, Magelang Regency, which is based on community service and based on the application of knowledge to refresh and increase social responsibility. This service aims to see community participation in Praja Bhakti activities in strengthening the integration of the nation. Community participation is quite high in an integrated manner through conventional information systems and communication infrastructure in Mangli Village. Praja Bhakti activities have a positive impact on people's understanding of the Indonesia’s Army and the Military Academy. The tangible form is strengthening the integration of the Indonesia’s Army and the Mangli Village People as an embryo of strengthening national integration which leads to strengthening national resilience and defense in the context of rural areas